Flight of fantasy : new perspectives on inner emigration in German literature, 1933-1945 - Donahue, Neil H. 1956-; Kirchner, Doris (Berghahn Books, 2003)
During the Nazi era many German writers chose, or were forced into, exile. Many others stayed and, after the end of this period, claimed to have retreated into "Inner Emigration". The nature of this kind of emigration and the underlying motives of these writers have been hotly debated to this day. Though the reception of Inner Emigration has often been confounded by disputes over the term itself, the issue is ultimately not a matter of nomenclature, but of more far-reaching issues of literary evaluation, moral discernment and the writing of history. This volume presents, for the first time, to an English-speaking readership the complexity of Inner Emigration through the analysis of problematic individual cases of writers who, under constant pressure from a watchful dictatorship to conform and to collaborate, were caught between conscience and compromise.